Conservative treatment in head and neck cancer - Žargi, Miha (Radiology and oncology (Ljubljana), 1997)
The incidence of head and neck cancer in Slovenia is increasing, especially inmale population. Late diagnosis, in advanced of disease, influences not onlythe treatment results but also the treatment strategies and modalities: aggressive surgery combined with radiotherapy and reconstructive procedures and chemotherapy in inoperable tumors is therefore indicated too frequently instead of organ sparing treatment. Early detection should be improved, especially in the target population, and all up-to-date diagnostic technology should be employed in centralized multidisciplinary pre-treatment assessment. Good co-operation between surgeons, radio and chemotherapists in planning, performing as well as in evaluating the treatment is also a basic condition for better implementation of organ sparing approaches in head and neck cancer.
Keywords: glava; rak (medicina); vrat; zdravljenje